Influence of Terminal Functionality on the Crystal Packing Behaviour and Cytotoxicity of Aromatic Oligoamides - Delfosse, Pierre; Seaton, Colin C.; Male, Louise; Lord, Rianne M.; Pike, Sarah J. (Frontiers in Chemistry, 2021)
The synthesis and characterization of three aromatic oligoamides, constructed from the same pyridyl carboxamide core but incorporating distinct end groups of acetyl (Ac) 1, tert-butyloxycarbonyl (Boc) 2 and amine 3 is reported. Single crystal X-ray diffraction analysis of 1-3 and a dimethylsulfoxide (DMSO) solvate of 2 (2-DMSO), has identified the presence of a range of intra- and intermolecular interactions including N-H⋯N, N-H⋯O=C and N-H⋯O=S(CH3)2 hydrogen-bonding interactions, C-H⋯π interactions and off-set, face-to-face stacking π-π interactions that support the variety of slipped stack, herringbone and cofacial crystal packing arrangements observed in 1-3. Additionally, the cytotoxicity of this series of aromatic oligoamides was assessed against two human ovarian (A2780 and A2780cisR), two human breast (MCF-7 and MDA-MB-231) cancerous cell lines and one normal human epithelial cell line (PNT-2), to investigate the influence of the terminal functionality of these aromatic oligoamides on their biological activity. The chemosensitivity results highlight that modification of the terminal group from Ac to Boc in 1 and 2 leads to a 3-fold increase in antiproliferative activity against the cisplatin-sensitive ovarian carcinoma cell line, A2780. The presence of the amine termini in 3 gave the only member of the series to display activity against the cisplatin-resistance ovarian carcinoma cell line, A2780cisR. Compound 2 is the lead candidate of this series, displaying high selectivity towards A2780 cancer cells when compared to normal PNT-2 cells, with a selectivity index value > 4.2. Importantly, against the A2780 cell line, this compound outperforms the clinical platinum drugs oxaliplatin by >2.6-fold and carboplatin by >1.6-fold.